Evaluation of percutaneous permeation of repellent DEET and sunscreen oxybenzone from emulsion-based formulations in artificial membrane and human skin - Tao Wang; Donald Miller; Frank Burczynski; Xiaochen Gu (Elsevier, 2014)
Insect repellent DEET and sunscreen ingredient oxybenzone play an essential role in minimizing vector-borne diseases and skin cancers. The purpose of this study was to investigate the effects of emulsion type, addition of thickening agent and droplet size in three emulsion-based lotions on percutaneous permeation of DEET and oxybenzone using in vitro diffusion experiments, in order to minimize overall systemic permeation of the substances. Formulation C (water-in-oil emulsion) significantly increased overall permeation of DEET through human skin (56%) compared to Formulation A (oil-in-water emulsion). Formulation B (oil-in-water emulsion with thickening agent xanthan gum) significantly decreased the size of oil droplet containing DEET (16%), but no effect on oil droplets containing oxybenzone. Adding xanthan gum also increased overall permeation of DEET and oxybenzone (21% and 150%) when compared to Formulation A; presence of both ingredients in Formulation B further increased their permeation (36% and 23%) in comparison to its single counterparts. Overall permeation of oxybenzone through LDPE was significantly higher by 26%-628% than that through human skin; overall permeation of DEET through human skin was significantly higher by 64%-338% than that through LDPE.